The Minskyan system, Part III: System dynamics modeling of a stock flow-consistent Minskyan model - Eric Temoigne (Levy Economics Institute of Bard College, 2006)
This is the last part of a three-part analysis of the Minskyan Framework. The paper presents a model that studies some of the features presented in Parts I and II. The model is Post-Keynesian in nature and puts a large emphasis on the role of conventions and the importance of the financial side. In doing so, it provides an innovative way to determine aggregate investment and to introduce nonlinearities in the modeling of Minsky's framework. This nonlinearity relies on the shifting property of conventions and the behavioral and psychological assumptions that they carry. Another specific characteristic of the model is that it is stock-flow consistent and explicitly takes into account the amortization of principal and refinancing loans. All of the modeling is done by using system dynamics, a flexible but rigorous modeling tool that gives the modeler a good understanding of the dynamics of complex models.
Keywords: E5; 330; Post-Keynesian economics; Minsky; financial fragility